HUBUNGAN ANTARA EARNINGS MANAGEMENT DAN CORPORATE ENVIRONMENTAL DISCLOSURE PADA PERUSAHAAN YANG TERDAFTAR DI BEI DAN MENGIKUTI PROPER PERIODE 2014-2015 - Lana Kamila; Senny Harindahyani (Perpustakaan Universitas Surabaya, 2018)
Abstract - The tendency will environmental awareness has brought a change of attitude toward the profit orientation of the environmental orientation of the company. Management as agents can not avoid the reality of the impact of corporate activity that not only generate profits and raise share prices, but also cause environmental impacts such as damage to ecosystems, pollution, effluents and waste and all of these are company responsibility in relation to the environmental aspects. This research is aimed to examine the influence of earnings management and corporate governance mechanisms to corporate environmental disclosure (CED). Earnings management was measure by discretionary accruals use Khotari et al. (2005) model. The population of this research is 51 companies in the non-financial companies which were listed in Indonesian Stock Exchange (IDX) in 2014-2015. Data used in this study come from annual reports and sustainable report of non-financial companies listed on the IDX and the Program for Pollution Control Evaluation and Rating (PROPER) in 2014-2015 with a total of 37 companies. Hypothesis testing method used is multiple regression analysis. Result of this research indicates that earnings management is negative significant of corporate environmental disclosure, and just board size variable can be moderate of earnings management and corporate environmental disclosure.